L22 ribosomal protein is involved in dynamin-related protein 1-mediated gastric carcinoma progression. Issue 3 (1st March 2022) - Cheng, Jianghong; Sha, Zizhuo; Zhang, Ruisan; Ge, Jinghao; Chen, Peng; Kuang, Xuefeng; Chang, Jiazhi; Ren, Kai; Luo, Xianyang; Chen, Shuai; Gou, Xingchun
ABSTRACT: Mitochondrial fission depends on dynamin-related protein 1 (Drp1) guanosine triphosphatase activity. Although there is some association between Drp1 and gastric cancer, the detailed mechanism remains largely unknown. In this study, the elevation of Drp1 was observed in human gastric carcinoma specimens including gastric mixed adenocarcinoma tissues, gastric intestinal-type adenocarcinoma tissues, and human gastric cancer cells compared to normal control, but not in diffuse gastric adenocarcinoma tissues. Gastric cancer patients with high Drp1 harbored advanced pathological stages and poor progression-free survival probability compared to those with low Drp1. Mdivi-1-mediated inactivation of Drp1 robustly inhibited cell viability and tumor growth but conversely induced cell apoptotic events in vitro and in vivo . Based on the Encyclopedia of RNA Interactomes Starbase, L22 ribosomal protein (RPL22) was recognized as the potential downstream oncogene of Drp1. Clinically, the significant correlation of Drp1 and RPL22 was also verified. Mechanistically, Drp1 inactivation did not affect the accumulation of RPL22 in gastric carcinoma. However, the intracellular distribution of RPL22 had an endonuclear location in Drp1-inactivated tumors. Of note, Drp1 inactivation notably reduced the expression of cytoplasmic RPL22 and increased its nuclear level in gastric cancer cells. Collectively, Drp1 had high levels in human gastric carcinoma specimens and could serve as a potential diagnostic and prognostic biomarker in gastric carcinoma. The Drp1 inactivation-mediated anti-proliferative and pro-apoptosis effects on gastric cancer were possibly associated with nuclear import of RPL22. This knowledge may provide new therapeutic tools for treating gastric carcinoma via targeting mitochondria-related ribosome pathway.